Indicator-Based Assessment of Marine Biological Diversity–Lessons from 10 Case Studies across the European Seas - Uusitalo, Laura; Blanchet, Hugues; Andersen, Jesper H.; Beauchard, Olivier; Berg, Torsten; Bianchelli, Silvia; Cantafaro, Annalucia; Carstensen, Jacob; Carugati, Laura; Cochrane, Sabine; Danovaro, Roberto; Heiskanen, Anna-Stiina; et al. (Frontiers in Marine Science, 2016)
The Marine Strategy Framework Directive requires the environmental status of European marine waters to be assessed using biodiversity as one out of 11 descriptors, but the complexity of marine biodiversity and its large span across latitudinal and salinity gradients have been a challenge to the scientific community aiming to produce approaches for integrating information from a broad range of indicators. The Nested Environmental status Assessment Tool (NEAT), developed for the integrated assessment of the status of marine waters, was applied to ten marine ecosystems to test its applicability and compare biodiversity assessments across the four European regional seas. We evaluate the assessment results as well as the assessment designs of the ten cases, and how the assessment design, particularly the choices made regarding the area and indicator selection, affected the results. The results show that only 2 out of the 10 case study areas show more than 50 % probability of being in good status in respect of biodiversity. No strong pattern among the ecosystem components across the case study areas could be detected, but marine mammals, birds, and benthic vegetation indicators tended to indicate poor status while zooplankton indicators indicated good status when included into the assessment. The analysis shows that the assessment design, including the selection of indicators, their target values, geographical resolution and habitats to be assessed, has potentially a high impact on the result, and the assessment structure needs to be understood in order to make an informed assessment. Moreover, recommendations are provided for the best practice of using NEAT for marine status assessments.